Pharmacoeconomic Evaluation of Cancer Biosimilars Worldwide: A Systematic Review - Huang, Hui-Yao; Liu, Cheng-Cheng; Yu, Yue; Wang, Le; Wu, Da-Wei; Guo, Lan-Wei; Wang, Shu-Hang; Fang, Hong; Bai, Ying; Fang, Yuan; Fan, Qi; Sun, Chao; et al. (Frontiers in Pharmacology, 2020)
Background and Purpose: The availability of oncology biosimilars is deemed as a fundamental strategy to achieve sustainable health care. However, there is scarce systematic evidence on economic effectiveness of cancer biosimilars. We aimed to synthesize evidence from pharmacoeconomic evaluation of oncology biosimilars globally, provide essential data and methodological reference for involved stakeholders. Materials and Methods: This systematic review was conducted in PubMed, Embase, the Cochrane library, CRD, ISPOR and NICE utill 31th December 2019. Information on basic characteristics, evaluation methodology and results were extracted. Quality of included studies was assessed using the Consolidated Health Economic Evaluation Reporting Standards Checklist. Results: For 17 studies identified (13 from Europe and 4 from US), the overall quality was generally acceptable. A total of 7 biological molecules involved with filgrastim, EPOETIN α, and trastuzumab leading the three. The mostly common evaluation perspective was payer, but the time horizon varied greatly. There were 10 studies which adopted cost minimization analysis to evaluate efficiency while 7 studies adopted budget impact analysis to address affordability, with cost ratio and cost saving being its corresponding primary endpoint. Although the comparability of included studies was limited and specific results were largely affected by uptake and price discount rates of the oncology biosimilar, the comprehensive results consistently favored its promotion. Conclusion: Globally, the economic evaluation of cancer biosimilars is in its initial phase. However, limited evidence from developed countries consistently supported both cost-effectiveness of efficiency and affordability of oncology biosimilars, while they were largely affected by uptake and price discount rate.